Horta escolar como estratégia para o desenvolvimento de uma educação ambiental crítica - Borges, Leonardo Alfaiate Ferreira (2024)
The environmental issue has become a major topic of discussion, especially in the face of growing concern about climate change, biodiversity loss and the impacts of human activities on the environment. For the insertion of this theme, the school emerges as an ideal environment for the development of environmental knowledge following a critical bias, therefore, Environmental Education – EE becomes a great opportunity to include students in actions aimed at the conservation of the environment and improvement of the quality of life. The educational institution is a privileged place to carry out practical actions that contribute to the formation of individuals who are more engaged and committed to the environment and to an ecologically balanced society. EE has proven to be an essential tool in bringing society closer to these issues in order to stimulate changes in behavior, attitudes towards the environment. In this sense, this research had as its general objective, to analyze the school garden as a learning strategy about the environmental system and the importance of its conservation. This analysis sought to understand how the application of EE content to the school garden can serve as an effective resource for critical environmental education and awareness about the importance of environmental conservation. The purpose of establishing a vegetable garden in the school environment is to sensitize students, volunteers, staff and the entire community to a systemic view of the environment and to value the existence of a productive "green area" in the school. To carry out the research, it was decided to adopt intervention research as the most appropriate methodology, supported by qualitative quantitative methods of an exploratory nature. The development adopted in this research is close to participatory research, as it provides a research path connected with educational action. Finally, the expectation is that this research will become a continuous initiative in the "laboratory" school and that it can be replicated, with the necessary adjustments in other school spaces, as the importance of contributing to the construction of a sustainable society has become evident. This is particularly relevant in the educational environment, as it is in these spaces that the formation of critical and conscious individuals occurs.